The Prevalence of Pemphigus (Razi Hospital and Department of Oral Pathology, Tehran University of Medical Sciences) - Eshghyar N; Eilanbo A (Tehran University of Medical Sciences, 1999)
The aim of this retrospective statistical study was to determine the prevalcence and frequency of"nage and sex distributions of pemphigus disease. Pemphigus disease classified as autoimmune bullous"ndermatoses which is a chronic mucocutaneous disease."nThis study was performed in Razi Hospital and department of oral pathology of dental school, Tehran"nUniversity of Medical Sciences. The most frequently effected area was buccal moucosa of oral cavity. The"nmost rate of recurrence was found in oral cavity which being more common in middle age females (25-44"nyears).